APPLYING RASCH MODEL TO MEASURE STUDENTS` READING COMPREHENSION - Dinar Pratama; Ihda Husnayaini (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2020)
There have been studies suggesting that students' reading comprehension in English subject is influenced by the accuracy of teaching strategy use. The use of appropriate teaching strategies is required to accommodate the diversity of students' abilities. Therefore, measurements are needed to provide actual information about students' abilities. This study aims to examine the levels of students' reading comprehension by using RASCH model. The subjects of this study were8th grade students, totaling 200 responses on the teacher's reading comprehension test with five alternative responses. The data analysis used was the Rasch 1 parameter model consisting of person reliability, item-person distribution maps, and item-person suitability. The findings of this study indicated that the average reading comprehension ability of students was included in the high category with a value (Meanperson) of 1.29 logits above the average level of difficulty of the test items (Meanitem) of 0. Further research is expected to be conducted to prove whether the addition of test items affect the value of person reliability.